Groundwater in the Arab Middle East - Wagner, Wolfgang. (Springer)
The book gives an outline of prevailing hydrogeologic conditions in the Arab Middle East together with the geologic background. Emphasis is given to relationships between the main features influencing the hydrogeologic conditions - regional geologic developments, paleogeographic conditions, morphology, climate and paleo-climate - and the resulting hydrogeologic features: formation of aquifers, distribution of major aquifers, main groundwater flow systems, occurrence of renewable and fossil groundwater. Reported data on hydraulic aquifer parameters, recharge rates and groundwater flow volumes are evaluated with a view to arrive at characteristic values under the specific hydrogeologic and climatic conditions. The area considered covers approximately the Arabian Plate. Information on the following countries is included: Bahrain, Iraq, Jordan, Kuwait, Lebanon, Oman, Qatar, Saudi Arabia, Syria, United Arab Emirates, West Bank and Gaza, Yemen. The arabian plate -- Northwestern mountain and rift zone of the northern arabian platform -- Eastern part of the northern arabian platform -- North arabian volcanic province -- Interior shelf -- Eastern arabian platform -- Arabian shield -- Oman mountains -- Aquifers in coastal plains of the arabian plate.